IN MEMORIAM DOCTOR DIRK FOK VAN SLOOTEN - SLOOTEN, DIRK FOK VAN (Research Center for Biology, 1954)
In the midst of his work Van Slooten has been suddenly called away at the relatively early age of 61.It was known that his heart was not too good,but it was expected that living a quiet life he would be able to finish his lifes work, the monograph of the Malaysian Dipterocarpaceae,to which he had been able since 1951 to devote all his time and concentration undisturbed by other duties.The striving towards the completion of this work on the most important family of Malaysian forest trees always occupied his mind and had been to a large extent the main object of his life.Van Slootens ambition was to produce careful work, meticulous in all details. This made him a slow worker, but at the same time one of the trustworthy kind. This trend towards perfectionism expressed itself equally in the preliminaries and routine work towards his objective.Through his method of working progress was steady but unfortunately relatively slow. Other factors beyond his control added to this result.Besides delays due to World War II, Van Slooten performed many other official duties in the same earnest way in which he carried out his research work. Any spontaneity and opportunism he had in his character was suppressed through his orderliness.Only in exceptional and very urgent circumstances would he make decisions Ã¡ 1improviste. It is of course questionable whether one can deduce a mans character from his published writings. Whether this thesis be accepted as a generality or not,it is certain that it held for Van Slooten. His care for details, for straight- forwardness, for trying to find the truth in his work found a remarkable parallel in his office work, and his private life. He wanted things to be clean and orderly. Even on excursions, which he made surprisingly seldom, his clothes were as speckless as they could possibly be in the circumstances.